Body mass index and physical fitness level of elementary school students - Allsabah, Muhammad Akbar Husein; Putra, Rendhitya Prima; Sugito (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2023)
The fitness condition of elementary school students is of particular concern in general, as today's technological advances and sedentary lifestyles greatly affect body mass index and physical fitness. This study aimed to determine the body mass index and physical fitness of elementary school students aged 10–12 years. The research method used in this study is a survey with a test approach and measurement of body condition. The subjects of this study used a population sampling technique by taking 1115 students from elementary schools in Kediri City and Regency. Research instruments used in the 2010 Indonesian Physical Fitness Test for children aged 10–12 years with 5 tests, namely 40 metres of running, bent elbow hanging test, sit-up test, upright jump test, vertical jump test, and 600-metre running test Measurement of body mass index (BMI) criteria in children aged 5–18 years based on height and weight owned by students The results of this study showed that male and female students in elementary schools in Kediri City and Regency got the results of the Body Mass Index (BMI) with a normal classification. The physical fitness results of male students in elementary schools in Kediri City and Regency show physical fitness results owned by sons with good classification. The physical fitness results of female students in elementary schools in Kediri City and Regency showed that most classifications were average. This study concludes that BMI and physical fitness must be maintained and improved. In the future, based on the results of this research, policies and methods will be needed so that BMI and student fitness will be even better.